Invariant-feature segmentation unlocks robust large-area mapping of mariculture - Ziyu Jiang; Jinyan Xie; Jihao Peng; Huaqing Wu; Yue Liu; Cong Zeng; Yueming Liu; Xiaomei Yang; Ling Cao (Marine Environmental Research, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Accelerated charge transfer dynamics via a CoFe bimetallic oxide hole transport medium for enhanced photoelectrochemical water oxidation - Jiaxin Mao; Xingyu Zeng; Yuming Wu; Ziyan You; Wenfang Deng; Ming Ma; Yueming Tan (Chemical Engineering Journal, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Epigenetic activation of lignin biosynthesis by CsJMJ16 confers enhanced resistance to Penicillium digitatum in citrus - Jing Zeng; Ting Li; Mengting Liu; Xiaoyan Duan; Jiechun Peng; Zhiwei Li; Guoxiang Jiang; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2026)

Exploring relaxation features for rapid identification of olive oil adulteration via low-field nuclear magnetic resonance integrated with chemometrics - Yulong Chen; Xuewen Qin; Shan Zeng; Bing Li; Yueming Tao; Huanjun Hu (Food Research International, 2026)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Changes in the spatial distribution of mariculture in China over the past 20 years - Yueming Liu; Zhihua Wang; Xiaomei Yang; Shaoqiang Wang; Xiaoliang Liu; Bin Liu; Junyao Zhang; Dan Meng; Kaimeng Ding; Ku Gao; Xiaowei Zeng; Yaxin Ding (Journal of Geographical Sciences, 2023)

A superpixel region merging based nonuniformity correction method for hyperspectral images - Xiaoyu Cheng; Zhouyin Cai; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

A spatial-spectral clustering-based algorithm for endmember extraction and hyperspectral unmixing - Xiaoyu Cheng; Zhouyin Cai; Jia Li; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)